Thermal diffusivity and conductivity of La 0.7Ca 0.3-xSr xMnO 3 (x= 0 to 0.10) - Alwi H.A.; Ewe L.S.; Ibrahim Z.; Ibrahim N.B.; Abd-Shukor R. (2023)
We report the room temperature thermal conductivity ? and thermal diffusivity ? of polycrystalline La 0.7Ca 0.3-xSr xMnO 3 for x = 0 to 0.1. The samples were prepared by heating at 1220 and 1320C. The insulator-metal transition temperature, T IM and thermal diffusivity increased with Sr content. Phonon was the dominant contributor to thermal conductivity and the electronic contribution was less than 1%. Enhancement of electrical conductivity ? and thermal diffusivity for x ? 0.08 was observed in both series of samples. The grain size of the samples (28 to 46 ?m) does not show any affect on the thermal and electrical properties. (2012) Trans Tech Publications.